2012
DOI: 10.1523/jneurosci.2921-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Central Adaptation to Odorants Depends on PI3K Levels in Local Interneurons of the Antennal Lobe

Abstract: We have previously shown that driving PI3K levels up or down leads to increases or reductions in the number of synapses, respectively. Using these tools to assay their behavioral effects in Drosophila melanogaster, we showed that a loss of synapses in two sets of local interneurons, GH298 and krasavietz, leads to olfaction changes toward attraction or repulsion, while the simultaneous manipulation of both sets of neurons restored normal olfactory indexes. We show here that olfactory central adaptation also req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…To verify if some enhancers are less susceptible to ectopic activity than others, we searched for Gal4 constructs whose activity in the mature adult brain is restricted to the brain. c105- Gal4 is active in a small number of cells during pupariation and adulthood [8] (see figure 4 g – i and electronic supplementary material, table S1) and GH298- Gal4 is active in local olfactory interneurons from larva and adult brain [31,32] (see figure 4 j – l and electronic supplementary material, table S1). Our G-TRACE data show that there are some GFP positive cells dispersed in the adult brain and two groups of cells that had transient activity of the enhancer c105 (figure 4 g – i , arrowheads).…”
Section: Resultsmentioning
confidence: 99%
“…To verify if some enhancers are less susceptible to ectopic activity than others, we searched for Gal4 constructs whose activity in the mature adult brain is restricted to the brain. c105- Gal4 is active in a small number of cells during pupariation and adulthood [8] (see figure 4 g – i and electronic supplementary material, table S1) and GH298- Gal4 is active in local olfactory interneurons from larva and adult brain [31,32] (see figure 4 j – l and electronic supplementary material, table S1). Our G-TRACE data show that there are some GFP positive cells dispersed in the adult brain and two groups of cells that had transient activity of the enhancer c105 (figure 4 g – i , arrowheads).…”
Section: Resultsmentioning
confidence: 99%
“…Activation/inhibition of PI3K or downstream elements of this pathway coherently regulate the number of synapses [ 28 29 ]. While the overactivation of PI3K-AKT signaling results in functional supernumerary synapses both in Drosophila and mammals [ 28 30 ], the overexpression of GSK3 causes a reduction of synapse number [ 28 , 31 32 ]. The pathway includes also the Jun kinase/AP-1 and Wnt signaling which are modulated by GSK3 [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Work in animal models has revealed that PTEN null mutant mice exhibit embryonic lethality, while the heterozygotes are highly susceptible to tumors [60]. Mammalian primary neuron cultures and Drosophila null mutants of PTEN show extensive dendritic arborization, which highlights the role of the PI3K/AKT/mTOR pathway in the regulation of neuronal growth [61,62]. Accordingly with the relationship between neuronal overgrowth and ASD, brain-specific conditional PTEN null mice develop dendritic hypertrophy, increased spine density and progressive macrocephaly confined to the affected brain areas.…”
Section: Ptenmentioning
confidence: 99%